FIRST CASE REPORT OF HEART FAILURE INDUCED BY DENGUE INFECTION IN RSUD JAGAKARSA - Cahyaningtyas, Tita Dwi; Ervina, Amelia (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Dengue cases in DKI Jakarta has increased in last 3 months with 6 death cases has been reported. Dengue virus (DENV) infection may be associated with increased risks of HF. We report a patient with DENV infection who developed HF on the 4th day of treatment. A-63th-year old woman was presented to hospital with four days of fever. There was no breath difficulty or bleeding manifestations. Hypertension was recorded as her past medical history. Diagnosis of dengue fever was made based on positive NS1 and decreased values of thrombocytes 138.000(Ht 50). Chest radiograph and electrocardiogram showed normal findings. On the fourth day of treatment, she complained of dyspnoea and orthopnoea without chest pain. Blood pressure was 220/120mmHg, pulse rate was 110/min, respiratory rate was 35/min, and peripheral oxygen saturation was 89% room air. Electrocardiogram shows sinus tachycardia and batwing appearance was found in chest radiograph. Echocardiography revealed decrease of the EFV to 43%. The patient then treated as heart failure and resulted in significant clinical improvement. The precise mechanism involved in the increased risk of HF by DENV is not thoroughly understood. HF induced by DENV infection may be underdiagnosed. Some studies have demonstrated that DENV directly infects cardiomyocytes leading to myocarditis. It also elevates proinflammatory cytokines, which interfere with ventricular contraction, resulting in HF. The difference of primary treatment for DENV infection and HF, make physician should raise awareness if their dengue patient complains of dyspnoea on exertion immediately after being diagnosed with DENV. This presented case demonstrated that DENV can be associated with increased risk in HF. Physicians should have more awareness of this and provide early management of HF while taking care of DENV infection patients.